Pandemia, ibridazione e il ruolo del Terzo settore. Un’analisi sul caso del Banco Alimentare - Libbi, Marco; Reggiardo, Anna (SocietàMutamentoPolitica, 2023)
The objective of this paper is to investigate the hybridization dynamics of the Third sector at the time of the Covid-19 pandemic. The progressive contamination between the State, market, family and Third sector spheres has long been subject of interest of the scholars. This paper aim at analysing these dynamics through the case study of Fondazione Banco Alimentare (Italian Food Bank Foundation). The case helps in investigating the impact of the pandemic on the role, logics and actors that make up the Third sector (both organizations and people) and its relation with the other subsystems. The empirical analysis shows that the pandemic and its consequences has enhanced the role of Fondazione Banco Alimentare, thanks to its relevance during the food emergency that also increased its visibility in the media. There are more institutional and non-institutional donors, more beneficiaries and help requests that resulted also in an accelerated professionalization and training of volunteers and employers. In conclusion, the Italian Food Bank and its network dealt with processes of digitalization, institutionalization and professionalization. These transformations resulted in a new positioning of the organization in the public sphere and redefined its relationship between local, national and European institutions.